Muḥammad, the Monk, and the Jews: Comparative Religion in Versions of the Baḥīrā Legend - Freidenreich, David M. (Entangled Religions, 2022)
Early Muslims told a tale about Baḥīrā, a Christian monk who identified the young Muḥammad as the long-awaited prophet and warned the boy’s guardian to protect him from murderous Jews. This legend proved so popular that not only later Muslims but also Christians, Samaritans, and Jews themselves retold it in widely divergent ways. This study analyzes the foundational version of the Baḥīrā legend that appears in the Sīra of Muḥammad ibn Isḥāq (d. ca. 768 CE) alongside others whose genealogical relationship to it is demonstrable. Within these tales, comparison functions as a powerful rhetorical tool by means of which premodern authors denigrate their targets. Academic comparison of the Baḥīrā legend’s many versions, in contrast, reveals the distinctive ways in which premodern authors from different communities understood the similarities and differences not only between their own community and its rivals but also among those rivals. This article demonstrates the utility of Oliver Freiberger’s methodological framework for comparative religion and, more specifically, the analytical value of juxtaposing sources in order to generate insights that deepen understanding of each comparand in its own right.